Resonance and reflection: revealing the philosophical significance of Bright Sheng's “My Other Song” from the concept of I-Ching - Fung Chiat, Loo; Qian, Deng (BP International, 2024)
This paper explores the philosophical significance and the illustration of I-Ching concepts that embedded in a solo piano works, “My Other Song,” composed in 2007 by Bright Sheng, a Chinese-American composer and one of the representatives of China's modern “New Wave” of composers. The philosophy of I Ching has a history of more than a thousand years, and the theory of yin and yang was derived which has been used by contemporary Chinese composers to innovate contemporary compositional methods. For example, Zhao Xiaosheng forms different combinations of pitch-class arrangements in the melody by decoding the hexagrams corresponding to the 64 hexagrams of the I Ching, while at the same time applying mathematical logic to the serial music styles of the I Ching and tonal structures [1]. By deconstructing the I-Ching concept in the musical works from a compositional point of view, how contemporary Chinese composers utilize the I-Ching-derived yin and yang theories for innovation becomes more clearly apparent. It is interesting to examine what are the approaches through which the I Ching concepts are integrated for a more contemporary style of musical work such as “My Other Song” composed in 2007? This paper examines the philosophical significance of ancient Chinese philosophy and Confucianism, the basic concepts of the I Ching, and the theory of yin and yang with regard to the philosophical implications in “My Other Song”. Through an analytical compositional perspective that encompasses pitch structure, tonality, intensity, theme, and musical gesture, it elucidates the relationship between these concepts and the yin-yang theory. The duality in the I Ching is both opposition and unity. The undulations of melody, variations of onality, and contrasts of intensity in musical compositions all imply traditional Chinese philosophical significance. How specific philosophical ideas are incorporated into the procedures and methods of musical composition, as well as the influence and significance of these ideas on modern music will be demonstrated in this article.